Challenges of the 21st Century: Implications for Sustainable Rangeland Restoration in the Dry Areas - Louhaichi, Mounir (2023)
Presentation on the implications of the challenges faced in the 21st century for sustainable rangeland restoration in dry areas. In addition to the limiting and successful factors that affected large-scale rehabilitation efforts. The presentation was performed by Mounir Louhaichi as a guest lecture on Exploring World Agriculture to students at the College of Agricultural Sciences at Oregon State University.